Succession Planning: Analysis Competence, Work Motivation, Strategic Leadership Development and Assessment Employee - Jumawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out what factors can support the success of succession planning in a corporate organization, this study uses a literature review of several articles related to dependent and independent, in this study does not use a questionnaire distribution involving respondents, the findings of this study are all variables independent variables significantly influence the dependent variable, so succession planning is successful if there is support or influence from the independent variables.